Corruption and the moral imperative, through the lens of Rizal - Diokno, Maria Serena I. (2011)
Rizal wrote at length about corruption in the 19th century, a malaise that ailed the country, and described it in terms of its perpetrators: friars, whose ubiquitous presence made them a fixture in daily life; Spanish secular officials at the top of the colony’s hierarchy; and local officials, Filipinos among them. Beyond rich descriptions of corruption, Rizal’s works and his correspondence with family, friends, and adversaries offer a rich panoply of meaning about colonial life, the nature of power within the Spanish patrimonial order, and Rizal’s understanding of the nation. The paper argues that his crusade against corruption was not simply a rejection of official waywardness but was central to the project of building the Filipino nation.
Keywords: Spain -- Colonies -- Philippines -- Administration, 1965-1986; Rizal, Jose ,1861-1896 -- Political and social views; Catholic Church -- History -- 19th century